Governance in Russian Regions A Policy Comparison (Springer International Publishing, 2018)
This book investigates the emergence and working of governance networks in contemporary Russia. Drawing on a case study design, it provides a novel comparison of seven policy issues each investigated across various Russian regions or over time. Its authors reveal that governance networks are a ubiquitous phenomenon emerging in different regime types. It sheds light on how and why state authorities interact with non-state actors and unravels various types, functions and flavours of governance networks in Russia. By precisely tracing how state authorities govern networks under the terms of a hybrid regime, special emphasis is placed on the analysis of 'meta-governance' tools. Moreover, the book allows for theorising on governance in an increasingly authoritarian regime and thus can also be read as a unique contribution to research on governance theory in general. Creating a clear analytical framework it reflects the richness of governance theory and offers fresh perspectives on the nature of hybrid and 'new' authoritarian regimes. This original work will appeal to students and scholars of Russian Studies, public policy, political science, sociology, and public administration.